Challenges and Opportunities for Halal Tourism in Banyumas - Sarpini, Sarpini; Aziz, Jamal Abdul (Ijtimā iyya Journal of Muslim Society Research, 2023)
The tourism sector is one of the sectors that has an important role in the Indonesian economy. Since the concept of halal tourism emerged in early 2010, various reactions have emerged to the development of halal tourism. This year, Indonesia won the title of Top Muslim Friendly Destination of the Year 2023 in the Mastercard Crescent Rating Global Muslim Travel Index (GMTI) 2023 in Singapore. Indonesia's halal tourism rose to number one from the previous number two. This increase is an extraordinary achievement. In 2021, Indonesia is ranked fourth and in 2022 second. As one of the regencies in Central Java located south of Mount Slamet, Banyumas has many natural tourist destinations. Diversity of tourism such as nature tourism, religious tourism, to educational tourism is available in Banyumas. The beauty of this tourism can be seen from the number of tourists both from within and outside the region who visit. The increase in Muslim tourists is an opportunity and challenge to improve the tourism sector in Banyumas. This research uses qualitative research methods. This qualitative research method is used as a research procedure that produces descriptive data. This research concludes that Banyumas Regency as one of the regencies in Central Java Province is known to have tourism potential that is very potential to be developed. The development of halal tourism in Banyumas still has many challenges, namely air transportation access is not yet available. Tourism destinations are not yet evenly distributed, many are concentrated in the Baturraden area. Facilities and infrastructure supporting tourism activities still need to be improved in quality and quantity. Tourism attractions are less varied. There have not been many promotional events carried out related to halal tourism. In addition to the challenges, there are certainly many opportunities for halal tourism in Banyumas, namely the strength of the natural and geographical conditions of Banyumas Regency, which is dominated by a fairly large mountainous area. There are many waterfalls and other water tourism attractions. Location on the South Java crossing route. There are several destinations with religious nuances.